The private equity edge : - Laffer, Arthur B. (McGraw-Hill, 2009)
In The Private Equity Edge, economics giant Arthur B. Laffer, along with value-building experts William J. Hass and Shepherd G. Pryor IV, combines the concepts of intrinsic value, macroeconomics, and incentives into a single strategy used by today's top value builders. You'll learn how to create value while reducing risk by: a) Thoroughly exploring relevant data to quantify ranges of value and risk; b) Anticipating reactions of those whom you seek to influence; c) Exploring possibilities and options before making major decisions; and d) Employing incentive systems that work in both up and down markets.